2019
DOI: 10.12659/msm.913839
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sleep Deprivation (SD) on Rats via ERK1/2 Signaling Pathway

Abstract: Background Sleep deprivation (SD) is common in humans, and sleep loss has a significant influence on health and produces related diseases. Orexin-A has been demonstrated to play a role in physiological processes, including feeding, sleep/wake cycle, and energy metabolism. The aim of this study was to investigate the effect of SD on rats and to define the underlying mechanism. Material/Methods We constructed an SD rat model. The Morris water maze test was used to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…In this study, a significant difference in the hippocampal APTw signal was observed in sleep-deprived rats than that in normal rats, but no significant difference was observed in the hippocampal volume. This finding indicates that the APTw signal can reflect alterations in the hippocampus more sensitively than the hippocampal volume, which was reported to reduce after 5 weeks of sleep deprivation . Notably, a hyperintensity was observed in the cerebral ventricle, which may be due to the artifacts generated by the cerebrospinal fluid flow.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In this study, a significant difference in the hippocampal APTw signal was observed in sleep-deprived rats than that in normal rats, but no significant difference was observed in the hippocampal volume. This finding indicates that the APTw signal can reflect alterations in the hippocampus more sensitively than the hippocampal volume, which was reported to reduce after 5 weeks of sleep deprivation . Notably, a hyperintensity was observed in the cerebral ventricle, which may be due to the artifacts generated by the cerebrospinal fluid flow.…”
Section: Resultsmentioning
confidence: 79%
“…This finding indicates that the APTw signal can reflect alterations in the hippocampus more sensitively than the hippocampal volume, which was reported to reduce after 5 weeks of sleep deprivation. 30 Notably, a hyperintensity was observed in the cerebral ventricle, which may be due to the artifacts generated by the cerebrospinal fluid flow. This sign reminds us that we should avoid including the cerebral ventricle when analyzing the APTw signal in the hippocampus.…”
Section: Resultsmentioning
confidence: 99%
“…Sleep deprivation affects the ability to concentrate, intake information and mediate that information through neuronal signalling, learn as well as process memories for consolidation. Furthermore, it is affected by the signalling and expression profiles of many biological molecules including the GPCRs[ 20 , 21 ]. These functions are related to the different stages of sleep and hence there are stage specific implications of sleep deprivation.…”
Section: The Dynamic State Of Sleepmentioning
confidence: 99%
“…In addition, proteins like Sirt1, PGC1, FOXO, p66shc, and poly (ADP-ribose) polymerase 1 (PARP1) (Eros et al 2017) are shown to participate in early vascular ageing (Harvey et al 2015). Scientific evidences strongly indicate that SD adversely affects the above-mentioned signalling molecules (Chang et al 2009;Sugiyama et al 1995;Vecsey et al 2012;Wang et al 2019). This spurt us to propose and interlink the impact of SD on brain vascular ageing.…”
Section: Sleep Deprivation Sleep Restriction and Sleep Disruptionmentioning
confidence: 99%
“…However, high levels of PARP-1 cause cell death. Increased protein levels of orexin-A, OX1R, OX2R and PARP-1 and decreased protein level of ERK1/2 are observed in the hippocampus of SD rats (Wang et al 2019). PARP1-1, the sensor of DNA damage, is a new melatonin-dependent regulator of senescence-associated secretory phenotype (SASP) gene induction on oncogene-induced senescence (OIS).…”
Section: Foxo Transcription Factorsmentioning
confidence: 99%